Screening and identification of host proteins interacting with Toxoplasma gondii SAG2 by yeast two-hybrid assay - Meng-Yee Lai; Yee-Ling Lau (Parasites & Vectors, 2017)
Abstract Background The identification of receptors or binding partners of Toxoplasma gondii from humans is an essential activity. Many proteins involved in T. gondii invasion have been characterized, and their contribution for parasite entry has been proposed. However, their molecular interactions remain unclear. Results Yeast two-hybrid (Y2H) experiment was used to identify the binding partners of surface antigens of T. gondii by using SAG2 as bait. Colony PCR was performed and positive clones were sent for sequencing to confirm their identity. The yeast plasmids for true positive clones were rescued by transformation into E. coli TOP 10F’ cells. The interplay between bait and prey was confirmed by β-galactosidase assay and co-immunoprecipitation experiment. We detected 20 clones interacting with SAG2 based on a series of the selection procedures. Following the autoactivation and toxicity tests, SAG2 was proven to be a suitable candidate as a bait. Thirteen clones were further examined by small scale Y2H experiment. The results indicated that a strong interaction existed between Homo sapiens zinc finger protein and SAG2, which could activate the expressions of the reporter genes in diploid yeast. Co-immunoprecipitation experiment result indicated the binding between this prey and SAG2 protein was significant (Mann-Whitney U-test: Z = -1.964, P = 0.05). Conclusions Homo sapiens zinc finger protein was found to interact with SAG2. To improve the understanding of this prey protein’s function, advanced investigations need to be carried out.